Analisis Gaya Kepemimpinan Transformasional Kepala Sekolah SD Kentungan Dalam Meningkatkan Mutu Pendidikan - Eni Septiani (Universitas Muhammadiyah Enrekang, 2020)
the purpose of this study is to determine the leadership used impoorving and develoving the quality of education. The method used in this researech is a qualitative method that is with a case study approach in which th researcher pluges directly into the field with the aim of seeing what phenonomene or problems occur in the school, the broblem which at the beginning served as the principal was in improving the quality of education. An issue that must be resolved or overcome by Ms. Suatni. Solving the positive impact was followed by the surrounding community including parents. The results showed that, principal of kentungan elementary scool uses transformasional leadership. In this case the kentungan elementary scool principal can change and improve the quality of education.